Interventions to reduce deaths in people living with HIV admitted to hospital in low- and middle-income countries: A systematic review. - Rachael M Burke; Hussein H Twabi; Cheryl Johnston; Marriott Nliwasa; Ankur Gupta-Wright; Katherine Fielding; Nathan Ford; Peter MacPherson; Elizabeth L Corbett (Public Library of Science (PLoS), 2023)
People living with HIV (PLHIV) admitted to hospital have a high risk of death. We systematically appraised evidence for interventions to reduce mortality among hospitalised PLHIV in low- and middle-income countries (LMICs). Using a broad search strategy with terms for HIV, hospitals, and clinical trials, we searched for reports published between 1 Jan 2003 and 23 August 2021. Studies of interventions among adult HIV positive inpatients in LMICs were included if there was a comparator group and death was an outcome. We excluded studies restricted only to inpatients with a specific diagnosis (e.g. cryptococcal meningitis). Of 19,970 unique studies identified in search, ten were eligible for inclusion with 7,531 participants in total: nine randomised trials, and one before-after study. Three trials investigated systematic screening for tuberculosis; two showed survival benefit for urine TB screening vs. no urine screening, and one which compared Xpert MTB/RIF versus smear microscopy showed no difference in survival. One before-after study implemented 2007 WHO guidelines to improve management of smear negative tuberculosis in severely ill PLHIV, and showed survival benefit but with high risk of bias. Two trials evaluated complex interventions aimed at overcoming barriers to ART initiation in newly diagnosed PLHIV, one of which showed survival benefit and the other no difference. Two small trials evaluated early inpatient ART start, with no difference in survival. Two trials investigated protocol-driven fluid resuscitation for emergency-room attendees meeting case-definitions for sepsis, and showed increased mortality with use of a protocol for fluid administration. In conclusion, ten studies published since 2003 investigated interventions that aimed to reduce mortality in hospitalised adults with HIV, and weren't restricted to people with a defined disease diagnosis. Inpatient trials of diagnostics, therapeutics or a package of interventions to reduce mortality should be a research priority. Trial registration: PROSPERO Number: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42019150341.